Impact of Age on Plasma Inflammatory Biomarkers in the 6 Months Following Mild Traumatic Brain Injury. Issue 5 (September 2020) - Thompson, Hilaire J.; Martha, Sarah R.; Wang, Jin; Becker, Kyra J.
Abstract : Objective: To compare plasma inflammatory biomarker concentrations to 6 months in young and older adults with and without mild traumatic brain injury (TBI). Setting: Level 1 trauma center. Participants: Younger (21-54 years) and older (55+) adults diagnosed with mild TBI along with age-/sex-matched noninjured controls ( n = 313). Design: Prospective cohort study. Main Measures: Multiplex assays were used to quantify concentrations of selected plasma inflammatory markers at day 0, months 1 and 6. Results: Persistent aging-related differences were found between control groups in concentrations of 4 cytokines up to 6 months. At day 0, interleukin-6 (IL-6), IL-8, and fractalkine were higher in the older TBI compared with older control as well as the younger TBI groups, while IL-10 was higher in older TBI compared with controls. At month 1, significantly higher concentrations of IL-8, fractalkine, and tumor necrosis factor-α (TNF-α) were seen. At 6 months postinjury, significantly higher concentrations of IL-6 and IL-8 were seen, while a lower concentration of IL-7 was found in older versus younger TBI groups. Conclusion: The neuroinflammatory signature that accompanies mild TBI in older adults differs from that of younger adults. The differences seen are notable for their roles in neutrophil attraction (IL-8), neuronal-microglial-immune cell interactions (fractalkine), and chronic inflammation (IL-6). Abstract : Supplemental Digital Content is Available in the Text.